Power Quality Disturbance Mitigation Using Filters Incorporating Neural Network Controller - Shilpa, R.; Puttaswamy, P.S (Asian Journal of Electrical Sciences, 2016)
Now a Days Harmonics in power systems is becoming a crucial issue due to the abrupt rise in the use of nonlinear loads. A Power Filter is one of the best answers to this problem.The filter performs the job by injecting compensatory currents that counteract them at the Point where seclusion has to be provided from non linearities. In order to infuse these compensatory currents unerringly,through the inverter which requires proper gating signals that trail the reference currents precisely through a controller. The reference current provides an estimation of the amount of harmonics. Consequently, perfect calculation of these reference signals foster generation of proper gating signals for the inverter are required.Accurate estimation is done using the P-Q theory, D-Q theory as well as the Adaline for Shunt and Hybrid Power Filter. DC Voltage across the capacitor is regulated using the PI controller and the Neural Network based control.